Pengaruh Kinerja Keuangan Terhadap Harga Saham Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia - Shulthoni, Moch.; Alfan Ainul Yaqin Aulia Rohim; Bayu Aprillianto (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
This study aims to analyze the impact of financial performance on the stock prices of consumer goods industry companies listed on the Indonesian Stock Exchange (IDX) from 2018 to 2022. The study uses quantitative analysis and secondary data from annual reports of companies listed on the IDX from 2018 to 2022 and data on company stock prices. The independent variables in this study are profitability, financial leverage, and earnings per share (EPS). Profitability is measured by the Return on Assets (ROA), the Debt measures financial leverage to Equity Ratio (DER), and the company's earnings per share is measured by EPS. The dependent variable in this study is the stock prices of the companies. The research sample consists of 55 companies selected through purposive sampling. The data analysis was conducted using the SPSS 24 application program, and various tests were performed. The study results show that profitability and market value positively and significantly affect stock prices. Financial leverage has a positive but insignificant effect on stock prices.